Optimization of Supercritical Fluid Extraction for the Recovery of γ-Oryzanol-Rich Extracts with Improved Bioactivity from Rice Bran - João P. Baixinho; Martim Cardeira; Andreia Bento-Silva; Ana Maria Carvalho Partidário; Ana Teresa Serra; Maria do Rosário Bronze; Naiara Fernández (Antioxidants)
Rice bran (RB) is a rice processing by-product recognized to be a source of bioactive compounds, including γ-oryzanol and fatty acids, which have interesting bioactivities such as antioxidant and anti-inflammatory effects. This study aims to optimize the supercritical fluid extraction process for recovering these high-value compounds from rice bran with improved bioactivity. A Central Composite Face-Centered Design was employed to optimize the extraction process by varying the temperature (40–80 °C) and pressure (200–500 bar). The optimal extraction conditions were identified at 500 bar and 62 °C that led to the extraction of 17.3% mass yield with 784.5 mg of fatty acids and 36.6 mg of γ-oryzanol per gram of extract, striking a balance between extraction yield and bioactive concentrations. When compared with conventional extractions with n-hexane, supercritical fluid extraction showed similar global yield (18.0 vs. 17.3%) and FA concentration (130.14 vs. 135.70 mg/g of RB) but higher selectivity and extraction yield for γ-oryzanol (18.0 vs. 36.4 mg/g extract; 3.3 vs. 6.3 mg/g of RB). Cellular antioxidant activity assays showed that both extracts reduced the quantity of reactive oxygen species (ROS) up to 50% in Caco-2 cells submitted to oxidative stress. Importantly, supercritical fluid extract was more effective in inhibiting colorectal cancer cell growth (EC50 = 0.9 mg/mL vs. 1.15 mg/mL) than the hexane extract, and this effect was more pronounced than that obtained for pure γ-oryzanol in the same concentration range. These findings highlight the potential of supercritical fluid technology to develop rice bran extracts with antioxidant and antiproliferative properties, underlining the promising applications of this technology in the field of natural product extraction.